Evaluation of TPACK Competencies Based on Gender, Education and Years in Teaching of Mathematics Lecturers in Indonesia - Nana Sepriyanti; Sasmi Nelwati; Fatimah Zahrah; Musthofa Musthofa; Nasikhin Nasikhin (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
This study evaluates the ability of mathematics lecturers in Indonesian universities to use TPACK (Technological Pedagogical Content Knowledge). It uses a Sequential Explanatory research method that integrates quantitative and qualitative approaches. The findings indicate that overall, the TPACK skills of mathematics lecturers in Indonesia are at a very good level (85,6%). The questionnaire data showed that the aspects of gender, length of teaching, and level of education had average scores of 85.2%, 85.5%, and 86.1%, respectively. Students' responses to lecturers' TPACK were also high, with an average questionnaire score of 85.1%. Further analysis showed no significant difference in the TPACK ability of mathematics lecturers based on gender, years of teaching, or level of education. However, partial analysis showed that female lecturers' CK and PK components were superior to male lecturers. This indicates a significant effect of gender partially on lecturers' TPACK. At the same time, the length of teaching and level of education does not have a significant impact either partially or jointly on the TPACK ability of mathematics lecturers in Indonesia. This study provides in-depth insights into the factors that influence the TPACK of mathematics lecturers, with important implications for professional development and improving the quality of learning in the Indonesian higher education context